3D insights into nickel converter matte phases: Direct observations via TEM and FIB SEM tomography - Thyse, E; Akdogan, G.; Olivier, E; O'Connell, J; Neethling, J; Taskinen, P.; Eksteen, Jacques (Elsevier, 2013)
A prior application of mineralogy to the analysis of nickel converter matte was based on two dimensional in-plane projections of three dimensional phase structures. Recent developments in electron microscopy have established suitable techniques to base further analysis on actual three dimensional projections. Focused ion beam scanning electron microscopy tomography in arrangement with transmission electron microscopy was considered suitable in acquiring three dimensional projections of nickel converter matte phase structures at the mesoscale with subsequent reconstruction for 3D visualization and analysis. Transmission electron microscopic section analysis was particularly useful in signifying that phase structures were geometrically arranged within an underlying nickel-sulfide microtexture. Tomography reconstruction and rendering of a rectangular particle volume allowed for color and grayscale based3D visualization of the nickel-sulfide microtexture, copper-sulfide and NiCu-alloy phase structures. Color based 3D visualization was specifically effective in assigning a cubic morphology to smaller alloy phase structures. Grayscale based 3D visualization of alloy phase structures illustrated compositional zones correlating to the presence of bright Pt-dominant cores and darker Ni-dominant rims. High-fidelity reconstruction of developed Pt-dominant lobes was produced illustrating insightful morphological detail. It would be important to consider the three dimensional insights gained to the downstream metallurgy of nickel converter matte.